2016
DOI: 10.4028/www.scientific.net/msf.870.404
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Structure of Diffusional Zinc Coatings Formed in Nanocrystallized Zinc Powders

Abstract: The results of the studies of phase formation and the structural state of diffusional zinc coatings formed in zinc powder with nanocrystallized surface of the particles are presented. The sequence of iron-zinc phases formation during the process has been established, which is the reciprocal of those obtained during the annealing of "hot dip" coatings. The microstructure of δ-phase in the coating, a change in its texture and structural parameters through the thickness of the coating have been studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In the previous works [17][18][19], the relationship between the coating thickness, phase and chemical composition of the surface layers is described in detail. The δ-phase (FeZn7-10) is present on the surface of the coatings with a thickness of 10 to 40 μm, and for the coatings with a thickness of 50 to 80 μm the ζ-phase (FeZn13) appears on the surface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the previous works [17][18][19], the relationship between the coating thickness, phase and chemical composition of the surface layers is described in detail. The δ-phase (FeZn7-10) is present on the surface of the coatings with a thickness of 10 to 40 μm, and for the coatings with a thickness of 50 to 80 μm the ζ-phase (FeZn13) appears on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…The galvanizing temperature was 450 °C, the duration was from 1 to 4 hours. The saturating mixture contained zinc particles with nanostructured oxide on the surface [15][16][17][18], which is a feature of the proprietary technology. The galvanizing technique is described in [15][16][17][18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the corrosion and mechanical properties of nanоgalvanized coatings have shown that the properties of coatings are determined by their composition and microstructure [8][9][10]. This article provides a comparative analysis of the technological capabilities of equipment to obtain the necessary corrosion and mechanical properties of diffusion zinc coatings based on structural studies of coatings obtained using various technological schemes.…”
Section: Introductionmentioning
confidence: 99%